2019
DOI: 10.1111/jvh.13244
|View full text |Cite
|
Sign up to set email alerts
|

Asian consensus recommendations on optimizing the diagnosis and initiation of treatment of hepatitis B virus infection in resource‐limited settings

Abstract: Asia has an intermediate‐to‐high prevalence of and high morbidity and mortality from hepatitis B virus (HBV) infection. Optimization of diagnosis and initiation of treatment is one of the crucial strategies for lowering disease burden in this region. Therefore, a panel of 24 experts from 10 Asian countries convened, and reviewed the literature, to develop consensus guidance on diagnosis and initiation of treatment of HBV infection in resource‐limited Asian settings. The panel proposed 11 recommendations relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…As recently reported in the Asian consensus recommendations on optimising the diagnosis and initiation of treatment for HBV infection in resource‐limited settings, 5 the expert panel reviewed the Asian, American and European guidelines on the initiation of treatment of compensated and decompensated cirrhotic individuals, and of non‐cirrhotic HBeAg‐positive and ‐negative individuals. It is recommended that anti‐viral therapy should be initiated in all HBV‐infected compensated and decompensated cirrhotic individuals with detectable serum HBV DNA levels, irrespective of their ALT levels and HBeAg status.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As recently reported in the Asian consensus recommendations on optimising the diagnosis and initiation of treatment for HBV infection in resource‐limited settings, 5 the expert panel reviewed the Asian, American and European guidelines on the initiation of treatment of compensated and decompensated cirrhotic individuals, and of non‐cirrhotic HBeAg‐positive and ‐negative individuals. It is recommended that anti‐viral therapy should be initiated in all HBV‐infected compensated and decompensated cirrhotic individuals with detectable serum HBV DNA levels, irrespective of their ALT levels and HBeAg status.…”
Section: Resultsmentioning
confidence: 99%
“…The authors also noted that in resource‐limited settings where HBV DNA assay may not be readily available or affordable, serology and biochemical tests may serve as alternatives. However, it must be recognised that HBV DNA quantification provides critical information—especially in the setting of disagreement between serology and biochemical tests—and remains a vital component in the decision‐making process for treatment initiation 5 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of serum hepatitis B virus (HBV) DNA and alanine aminotransferase (ALT) are two of the main factors to determine treatment initiation for chronic HBV infection in the recently published East Asia Consensus, 1 and in other official guidelines. [2][3][4] Serum ALT and aspartate aminotransferase (AST) levels are commonly evaluated for other aetiologies of liver injury. Our previous study found that elevated AST and AST/ALT ratio are associated with poor overall survival for patients with hepatocellular carcinoma (HCC) after hepatic resection.…”
Section: Letter: Elevated Hbv Dna Predicts Poor Survival In Hepatocelmentioning
confidence: 99%